Teachers’ Perceptions of Artificial Intelligence Utilization in English Language Teaching at an Islamic Boarding School - Fajar Wirawan; Loly Novita; Widi Syaftinentias (Arus Jurnal Psikologi dan Pendidikan, 2026)
The development of Artificial Intelligence (AI) has influenced English language learning by providing various tools such as ChatGPT, Grammarly, and Duolingo. This study aimed to explore teachers’ perceptions of AI use in English language learning at an Islamic senior high school in Pekanbaru. A descriptive qualitative method was employed, involving English teachers selected through purposive sampling. Data were collected through interviews, observations, and documentation and analyzed using data reduction, data display, and conclusion drawing. The findings revealed that teachers generally had positive perceptions of AI. They believed that AI helped improve students’ vocabulary, grammar, pronunciation, and learning motivation. AI also assisted teachers in preparing learning materials and creating interactive learning activities. However, several challenges were identified, including limited technological skills, internet access issues, and concerns about students’ overreliance on technology. The study concludes that AI can effectively support English language learning when used appropriately and responsibly by teachers.